Peran Koperasi Merah Putih Dalam Pemberdayaan Ekonomi Masyarakat Desa - Diana Dwi Putri; Hendra Riofita (Jurnal of Management and Social Sciences, 2026)
This study aims to examine the role of the Merah Putih Village Cooperative (KDMP) in strengthening the village economy, using the lens of good governance and social capital. This study uses a qualitative method with a library research approach, referring to academic journals, books, and government policy documents as sources of information. The research shows that KDMP plays a significant role in improving the welfare of village communities by strengthening productive businesses, expanding access to capital, creating job opportunities, and developing local economic potential. The application of good governance principles such as transparency, accountability, and community participation is a crucial factor in the successful management of the cooperative. In addition, social capital such as mutual assistance, trust, and community collaboration also contribute to the sustainability of the village cooperative. However, the implementation of KDMP still has a number of challenges, including a shortage of human resources, limited cooperative management, and low digital literacy. Therefore, government support and capacity building of cooperative managers are crucial for KDMP to function as a tool for sustainable village economic development